Study protocol: Project 2VIDA! SARS-CoV-2 vaccine intervention delivery for adults in Southern California - Skaathun, Britt; Salgin, Linda; Muñoz, Fatima A.; Talavera, Gregory A.; Smith, Davey M.; Stockman, Jamila K.; O’Bryan, Sophie E.; Ramirez, Daniel; James-Price, Cynthia; Servin, Argentina E. (Frontiers in Public Health, 2024)
Background To date, the United States (US) leads the world in the number of infections and deaths due to the Coronavirus Disease 2019 (COVID-19). Racial and ethnic disparities in COVID-19 morbidity and mortality are staggering. Age-adjusted data show that AA and Latino individuals have had higher rates of death over most of the pandemic and during surges. Project 2VIDA! is community-based participatory research (CBPR) that was developed to address individual, social, and contextual factors related to access and acceptance of the COVID-19 vaccine among African American and Latino communities in Southern California. This paper describes the study protocol and overarching objectives. Methods and design Project 2VIDA! is a multilevel intervention that builds on the principals of CBPR and is designed to increase uptake of the COVID-19 vaccine among African American and Latino individuals (≥16 years and older) in San Diego County. The intervention was developed with a working group comprised of representatives from community and academia and centers on targeted COVID-19 individual awareness and education, linkage to medical and supportive services, COVID-19 community outreach and health promotion and offering the COVID-19 vaccine through community pop-up clinics. Discussion Findings from 2VIDA! will provide data on the impact, feasibility, and acceptability of the intervention which are all crucial for the adaptation, refinement, and improvement of vaccine outreach interventions for COVID-19 and other vaccine preventable infectious diseases that severely impact African American and Latino communities. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT05022472?term=Project+2VIDA&draw=2&rank=1, NCT05022472.